Can Portugal become a leader in offshore wind power? How to achieve a competitive advantage in this industry - Boas, Duarte da Silva Vilas (2024)
This project explores whether Portugal can lead the offshore wind power industry and achieve a competitive edge. It evaluates Portugal's strategic advantages, including its geographical location, industrial capabilities, and supportive government policies. The analysis identifies key trends, economic viability, supply chain dynamics, industry challenges, and necessary technological advancements. By mapping the global ecosystem of main industry players, it examines potential partnerships and stakeholder engagement to foster innovation and address challenges. Recommendations focus on infrastructure investment, regulatory streamlining, and enhancing collaboration to position Portugal at the forefront of the offshore wind sector.